Intravenous magnesium sulphate as an adjuvant in acute severe asthma refractory to conventional therapy - Sahoo, Aswini Kumar; Mohapatra, SC (Asian Journal of Medical Sciences, 2014)
DOI: http://dx.doi.org/10.3126/ajms.v6i1.9609 Asian Journal of Medical Sciences Vol.6(1) 2015 134-135